Extending the common information model for smart grids operational computations based on bus-branch models. (2018) - Celotto, Antonio; Falco, Massimo De; Gallo, Mariacristina; Vaccaro, Alfredo
In the modern smart grids (SGs), the heterogeneity of elements makes their interoperability difficult. In order to facilitate the integration and the interaction between different types of elements, the International Electrotechnical Commission (IEC) has introduced some standards (e.g., CIM, SCL), aimed at defining a common language for the communication among the different elements of a power system. However, without a harmonisation of these standards, the development and the implementation of systems and applications will result in a noticeable amount of single engineering design schemes. An ontology-based approach could collect knowledge from different applications, bridging the gap of harmonisation among such models. This paper deals with the implementation of a CIM ontology based on a bus-branch model that aims to support the power system state estimation problem. Resulting ontology has been instantiated by using a case study on a real power flow problem and evaluated by applying some well-known metrics.